The composition of red mason bee cocoons. Issue 2 (15th March 2022) - Murawska, Agnieszka; Migdał, Paweł; Zajdel, Barbara; Popiela, Ewa; Roman, Adam
Abstract: This study aimed to determine the proximate composition, gross energy, and amino acid amounts and mineral content in red mason bee Osmia bicornis (syn. Osmia rufa) cocoons to define their possible uses. This is the first study documenting the proximate composition and amounts of amino acids in Osmia bicornis cocoons. Like all other insect cocoons, red mason bee cocoons consist of silk. Samples were analyzed using AOAC standard methods. The dominant component of the examined cocoons was crude protein, which accounted for 52.91%. The examined cocoons were found to contain a considerable amount of crude fiber (30.69%)(consisting of NDF – 54.03% and ADF – 45.97%). Red mason bee cocoons consisted of 18 amino acids, including 39% of essential amino acids (EAA). The examined cocoons contained a significant amount of minerals. It appears from comparing the obtained results with other sources of dietary fiber in products of insect origin, that the Osmia bicornis cocoon differs in its composition. However, this fact may indicate its unique properties.